SOLITARY SPLENIC METASTASIS OF COLON CANCER: A CASE REPORT - Sh. Hashemzadeh M. Safari (Acta Medica Iranica, 2004)
Although splenic metastasis is fairly common in disseminated cancer, solitary splenic metastasis in the absence of diffuse dissemination is rare. We report a case of 44 year-old man who developed isolated splenic metastasis of colon cancer. The patient had undergone right sided hemicolectomy for colon cancer in 1988. In 2001, he underwent reoperation because of local recurrence of tumor in the anastomotic site. The patient was admitted to our hospital on Sep 2003 with abdominal pain. Chest X-ray was normal. Abdominal CT scan showed a large cystic lesion in the spleen. Splenectomy was performed for the patient. The spleen was enlarged, firm and irregular. Histological examination showed metastatic mucinous adenocarcinoma. Based on this case, we recommend that clinicians consider possibility of metastasis in cystic lesions of spleen, especially in patients with a history of a malignant disease.